Biosynthesis of Zinc Oxide Powder Using Sandoricum koetjape Peel Extract at Various Annealing Temperature - Rini, Ari Sulistyo; Hidayanti, Nurul; Rati, Yolanda (Fakultas Matematika dan Ilmu Pengetahuan Alam, Univetsitas Tanjungpura, 2021)
Zinc oxide (ZnO) synthesized with natural reductants has attracted the attention of researchers because it is environmentally friendly and non-toxic. In this study, ZnO was prepared using Sandoricum koetjape (S. koetjape) peel extract. An aqueous extract of S. koetjape peel was used as biological reduction agent for the synthesis of ZnO from zinc nitrate hexahydrate. The ZnO powder obtained was annealed at different temperatures i.e, 300°C, 400°C, and 500°C for 1 hour. Structural, morphological, optical properties, and functional groups of samples were analyzed using X-Ray Diffraction, Scanning Electron Microscopy, UV-Vis Spectroscopy, and Fourier Transform Infrared Spectroscopy, respectively. The X-ray diffraction pattern shows that pure hexagonal wurtzite structure of ZnO particles can be achieved after annealing. The crystal size has also increased with increasing annealing temperature. SEM photo demonstrates the transformation of ZnO particle from spherical to microflower due to annealing. The widest absorption peaks in the UV-Vis spectrum was occurred after annealing at 500°C. The bandgap energy of ZnO increases after annealing from 3.08 eV to 3.20 eV. The FT-IR analysis confirms O-H functional group from extract has been decomposed due to the annealing process. Based on this study, biosynthesized ZnO using Sandoricum koetjape peel extract requires annealing process to improve the purity, enhance the light absorbance and change the microstructure of ZnO.